Efforts to Improve the Ability to Read the Qur'an Using the WAFA Book Method at Usman Al-Farsy Plus Kindergarten - Nurul Arifin, Rifatul Hasanah; Dewi Pusparini; Khozaimah; Ani Fitriyah; Robiatul Adawiyah; Qurrotul Uyun (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
This study aims to improve the ability to read the Qur'an of early childhood children in Usman Al-Farsy Plus Kindergarten through the application of the Wafa book method. This method uses the Quantum Teaching approach that integrates multisensory-based learning, such as songs, movements, and visual aids. This study uses the Classroom Action Research (CAR) model with the Kemmis and Taggart design, involving 22 children in group A as research subjects. The results showed a significant increase in the ability to read the Qur'an after the application of the Wafa book method. In the pre-cycle, only 27% of children reached the "Developing According to Expectations" (BSH) category. This figure increased to 50% in cycle I and reached 73% in cycle II. A gradual approach, the use of Hijaz songs, and cooperation with parents are key factors for success. This study recommends the Wafa book method as an effective alternative to improve Qur'an reading skills at the early childhood education level.